2019
DOI: 10.1159/000495190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histochemical, and Molecular Study of Three Turkish Siblings Diagnosed with H Syndrome, and Literature Review

Abstract: Background: The term “H syndrome” was coined to denote the major clinical findings, which include hyperpigmentation, hypertrichosis, hearing loss, hepatosplenomegaly, hyperglycaemia, hypogonadism, hallux flexion contractures, and short height. Objective: To report the clinical, endocrinological, histochemical, and genetic findings of three siblings. Methods: Skin and liver biopsies were taken to investigate the histochemical characteristics of hyperpigmented hypertrichotic skin lesions and massive hepatomegaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Similar to what Enver Simsek8 found in three Turkish siblings with H-syndrome, our patient had early-onset sensorineural hearing loss, hallux valgus (figure 2B), bilateral medial thigh hyperpigmentation/induration, hypertrichosis, dilated scleral vessels, short stature, microcytic hypochromic anaemia, raised inflammatory markers and SLC29A3 mutation. Our patient exhibited pericardial thickness instead of mitral valve/ Atrial Septal defect cardiac problems, did not have type I diabetes but did have a pancreatic exocrine deficiency and had normal secondary sexual characteristics, in contrast to theirs.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to what Enver Simsek8 found in three Turkish siblings with H-syndrome, our patient had early-onset sensorineural hearing loss, hallux valgus (figure 2B), bilateral medial thigh hyperpigmentation/induration, hypertrichosis, dilated scleral vessels, short stature, microcytic hypochromic anaemia, raised inflammatory markers and SLC29A3 mutation. Our patient exhibited pericardial thickness instead of mitral valve/ Atrial Septal defect cardiac problems, did not have type I diabetes but did have a pancreatic exocrine deficiency and had normal secondary sexual characteristics, in contrast to theirs.…”
Section: Discussionsupporting
confidence: 87%
“…SLC29A3 encodes a nucleoside transporter which plays a significant role in the cellular uptake of nucleosides and nucleobases. It was previously reported that many diseases were related to RAD51AP1 expression, including autoinflammatory diseases [ 46 ], H syndrome [ 47 ], insulin-dependent diabetes [ 48 ], pigmentary hypertrichosis, autoimmune insulin-dependent diabetes mellitus [ 49 ], and sclerosing bone dysplasias [ 50 ]. Meanwhile, MIMT1 is an MER1 repeat-containing imprinted transcript, which can undergo hypermethylation in the placenta of intrauterine growth-restricted fetuses in cattle [ 51 ], and truncation of exons 3 and 4 of the MIMT1 gene caused intrauterine growth restriction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among several features defining SLC29A3 spectrum disorder, cutaneous findings are considered to comprise the hallmark clinical presentation ( 1 , 2 ). Almost all patients reported in the literature presented with different musculoskeletal and/or dermatological phenotypical characteristics, including hyperpigmentation, hypertrichosis, facial telangiectasias, flexion contractions, or foot deformities ( 2 , 4 , 6 , 9 , 15 , 16 ). Diabetes was the first and only presenting feature in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of empirical treatment trials for SLC29A3 spectrum disorders in the literature, tocilizumab (8 mg/kg/d), a human monoclonal interleukin-6 receptor antibody, was administered ( 6 , 15 , 16 ). However, the anemia did not improve, and transaminase levels increased 2-3-fold after two doses of this hepatotoxic agent.…”
Section: Case Presentationmentioning
confidence: 99%